PENGENDALIAN PERSEDIAAN GAS LPG DI PT. ANUGRAH GAS UTAMA DENGAN MENGGUNAKAN METODE PERIOD ORDER QUANTITY DAN JUST IN TIMEETODE PERIOD ORDER QUANTITY DAN JUST IN TIME - Syarifudin, Achmad; Puji Astuti, Annisyah; Khadijah, Afni; Gunawan, Wawan (Jurnal Intent: Jurnal Industri dan Teknologi Terpadu, 2025)
PT. Anugrah Gas Utama is a company that cooperates with Pertamina or commonly called the LPG Bulk Filling and Transportation Station (SPPBE) which is engaged in oil and gas or oil and gas which produces 3 kg of gas.  In the implementation of production, PT. Anugrah Gas Utama requires raw material inventory control from time to time to ensure a smooth production process, with the raw material control system implemented in the company, the inventory costs can be reduced as little as possible. The purpose of this study was to determine the optimal number of orders for raw materials and to minimize total inventory costs. Based on the research results obtained by using the Period Order Quantity (POQ) and Just In Time (JIT) methods, it can be seen that the lowest total cost is by using JIT which is Rp.31,674,517 while using the POQ method is Rp.212,331. 595. Because the JIT method has a lower total cost than the POQ method, the Just In Time (JIT) method can be used by companies. But the company must reduce its inventory and build strong relationships with suppliers and customers.